Analisis Kinerja Keuangan pada Koperasi Usaha Warga Pupuk Kujang Periode 2018-2022 - Karismawati, Dwi Yunita; Sihabudin; Robby Fauji (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research analyzes the financial performance of the Koperasi Usaha Warga Pupuk Kujang Cikampek during 2018–2022, focusing on financial ratios such as liquidity, solvency, profitability, and activity. Using a quantitative descriptive approach, the study employs annual financial data to identify trends and factors influencing performance. Findings reveal significant fluctuations in the cooperative's financial ratios over the examined period. While liquidity ratios fluctuate, solvency ratios show improvement over time, indicating efficient debt management and asset utilization. However, profitability ratios exhibit a declining trend, emphasizing the need for measures to enhance revenue generation and cost management. Meanwhile, activity ratios depict gradual improvement, indicating enhanced operational efficiency. The implications suggest the importance of careful monitoring, risk management, and strategic initiatives to ensure sustainable growth and financial stability for Koperasi Usaha Warga Pupuk Kujang Cikampek.